Spirit Name (Ishina Lya Mupashi) and Strong Artificial Intelligence (Strong AI): A Bemba Theo-Cosmology Turn - Kaunda, Chammah J. (Theology today, 2021)
This article probes the prospects of personhood in strong artificial intelligence (Strong AI) from a Bemba theo-cosmological perspective. Employing an interdisciplinary perspective, it argues that the Bemba concept of spirit name (ishina lya mupashi) can make a constructive contribution to a theo-cosmology of the possibility of the personhood of strong AI. This article shifts the discussion from individualized superhuman-intelligence informed to eco-relational intelligence personhood-shaped strong AI.